Coronal Displacement of Cementum in Impacted Teeth and Its Correlation to Age: A Preliminary Study - Aparna Thombre Sharma; Minal Chaudhary; Vivek Thombre; Satyajit A Tekade; Pranoti Pradhan; Kriti Bagri (Wolters Kluwer Medknow Publications, 2010)
Structural changes occur throughout life in enamel, dentine, and cementum with continuous cementum apposition. Erupted teeth are directly affected by environmental and ageing process as opposed to impacted teeth. Cementum deposition on a healthy tooth is a continuous process and relationship may exist between age and cementum thickness. Cementum deposition may occur with coronal displacement due to erupted forces on impacted teeth. Aim: The present study was designed to investigate the extent of coronal displacement of cementum in impacted teeth as compared to erupted teeth, and to draw a probable correlation between age and coronal displacement of cementum in erupted and impacted teeth. Materials and methods: A morphometric analysis was performed using Leica DML B2 O-Win Lite image analysis system. Results: Our results suggested that there was a significant linear and positive correlation between age and coronal displacement of cementum in impacted mandibular third molars. Conclusion: This method can be applied in the arena of forensic odontology.